The Dose Makes the Poison - Dynamic Pricing Strategies and Their Influence on Consumers - Thomas Rudolph; Gianluca Scheidegger; Elias Barth; Marc Linzmajer (Marketing Review St.Gallen, 2019)
To study price dynamics of the Swiss online retail market, prices of 1200 products from 299 retailers were observed for 50 days. The authors identified four dynamic pricing strategies, compared the price changes of pure online and cross-channel retailers and measured how dynamic pricing influences retailers' value for money ratings.
Keywords: 650